1989
DOI: 10.3164/jcbn.6.195
|View full text |Cite
|
Sign up to set email alerts
|

Influence Dietary Riboflavin Deficiency on Lenticular Glutathione Redox Cycle, Lipid Peroxidation, and Free Radical Scavengers in the Rat

Abstract: (first set of animals) or 0.05 M sodium phosphate buffer, pH 7.2 (second set of animals) using a Potter/Elvehj am glass homogenizer. A 7.5% homogenate was prepared from two lenses (third set of animals) in 5% ice-cold TCA. Aliquots of J. Clin. Biochem. Nutr. INFLUENCE OF RIBOFLAVINDEFICIENCY ON RAT LENS 197 the lens homogenate (Tris-EFTA buffer) were analysed for GSH and GSSG measured fluorimetrically [11] in a Hitachi 650-lOS spectrofluorimeter and for total and non-protein sulfhydryl groups with Ellman'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0
2

Year Published

1990
1990
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
(50 reference statements)
0
11
0
2
Order By: Relevance
“…Bate et al (27) also reported elevated lipid peroxidation in riboflavin deficiency with no change in glutathione levels and GPx activity. Moreover, in some studies, an increased GPx activity was observed simultaneously with increased lipid peroxidation in riboflavin deficiency (22,29,40) . As has been mentioned previously, this increased GPx activity, most probably, is a compensatory response to increased lipid peroxidation occurring in riboflavin deficiency.…”
Section: Human Studiesmentioning
confidence: 97%
See 2 more Smart Citations
“…Bate et al (27) also reported elevated lipid peroxidation in riboflavin deficiency with no change in glutathione levels and GPx activity. Moreover, in some studies, an increased GPx activity was observed simultaneously with increased lipid peroxidation in riboflavin deficiency (22,29,40) . As has been mentioned previously, this increased GPx activity, most probably, is a compensatory response to increased lipid peroxidation occurring in riboflavin deficiency.…”
Section: Human Studiesmentioning
confidence: 97%
“…The only human study published has reported no significant difference in erythrocyte glutathione concentrations between normal and riboflavin-deficient subjects ( 26 ) . Furthermore, some animal studies also did not report any change in glutathione content in different tissues (such as the liver, lens and erythrocytes) in riboflavin-deficient animals ( 27 29 ) . A mechanism for the unchanged tissue glutathione content in riboflavin deficiency could be the increased biosynthesis of glutathione from its precursor amino acids as a compensatory action ( 30 ) .…”
Section: Role Of Riboflavin In the Prevention Of Lipid Peroxidationmentioning
confidence: 98%
See 1 more Smart Citation
“…Alteration in energy metabolism due to mitochondria dysfunction is one of the major causes of paclitaxel-induced peripheral neuropathy. 18) Neurons require large amounts of energy to transport neuronal transmitters in axons. Flavin mononucleotide (FMN) and FAD, which are derived from riboflavin, are used for the electron transport chain to produce ATP, the primary energy carrier in cells.…”
Section: Discussionmentioning
confidence: 99%
“…The studies on Indians revealed that inadequacies of certain micronutrients, such as riboflavin, zinc and copper, were associated with cataract [13,14] . In undernourished patients, the proportion of insoluble proteins in the lens was found to be significantly higher as compared to well-nourished cataract patients, indicating a decreased solubility of soluble proteins, a common finding in nuclear cataracts [15] .…”
Section: Linkages Of Macronutrients Micronutrients and Antioxidants mentioning
confidence: 99%